(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This work extends the non-central Stirling numbers of the second kind to complex arguments. This extension is achieved through an integral representation employing a Hankel contour. Furthermore, we investigate the extent to which key properties, including the recurrence relations, of the classical Stirling numbers are preserved under this complex generalization.